Exposure to School Bullying and Psychological Health in Young Adulthood: A Prospective 10-Year Follow-Up Study. (3rd April 2018) - Östberg, Viveca; Modin, Bitte; Låftman, Sara Brolin
ABSTRACT: Being bullied at school is strongly related to psychological health complaints at the same time point. Studies have also found long-term associations, but few have combined a prospective design with children's own reports on bullying, and conducted gender-specific analyses. The present study assesses health consequences in young adulthood of self-reported victimization in adolescence using data from Child-LNU in 2000 and the follow-up in 2010 (including 63% of the original sample, n  = 813). At ages 10–18 a clear cross-sectional association was found for both girls and boys. Among girls, exposure to bullying also predicted psychological complaints 10 years later, at ages 20–28 (OR = 2.86). This association was not explained by socioeconomic circumstances, neither in adolescence nor in young adulthood. Instead, it can partly be understood as victimization, among adolescent girls, being associated with negative self-image and psychological health as well as with deficits in social resources more generally.